Digital data integrity : - Little, David B. (John Wiley, 2007)
Digital Data Integrity throws light on the data integrity landscape of the future. It provides the reader with a brief overview of the historical methods and subsequent evolution of data protection. The text shows how the whole subject of data integrity is changing and describes and positions many of the new, enhanced, more intelligent protection technologies and methods.